2015
DOI: 10.1111/joic.12251
|View full text |Cite
|
Sign up to set email alerts
|

Low On‐Treatment Platelet Reactivity Predicts Long‐Term Risk of Bleeding After Elective PCI

Abstract: MAE ADP test before and after PCI, was associated with any, and BARC ≤ 2 bleeding after elective PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Platelet reactivity varies in percutaneous coronary intervention (PCI) patients treated with clopidogrel ( 1 ), and platelet participates in thrombosis and bleeding events. Previous studies have established in patients with coronary heart disease (CHD) that high on-treatment platelet reactivity (HTPR) is an independent risk factor for thrombotic events ( 2 4 ), while low on-treatment platelet reactivity (LTPR) is an independent risk factor for bleeding events ( 5 8 ). Therefore, platelet reactivity controlled within normal range might contribute to the reduction of thrombosis and bleeding events in patients with CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Platelet reactivity varies in percutaneous coronary intervention (PCI) patients treated with clopidogrel ( 1 ), and platelet participates in thrombosis and bleeding events. Previous studies have established in patients with coronary heart disease (CHD) that high on-treatment platelet reactivity (HTPR) is an independent risk factor for thrombotic events ( 2 4 ), while low on-treatment platelet reactivity (LTPR) is an independent risk factor for bleeding events ( 5 8 ). Therefore, platelet reactivity controlled within normal range might contribute to the reduction of thrombosis and bleeding events in patients with CHD.…”
Section: Introductionmentioning
confidence: 99%
“…ORs for bleeding or transfusion with impaired platelet aggregation were moderate or had wide confidence intervals. 83,88,92,94 However, two studies, which are not presented in ►Table 6 due to low rating, reported somewhat different results. Preisman et al investigated patients on clopidogrel undergoing cardiac surgery and reported AUC 0.81 for preoperative Multiplate ADP-induced aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…Fully described, treatment standardized or randomized Each point is either "fulfilled" (1) or "not fulfilled" (0) Notes: A3: "Fulfilled" when patient inclusion was described as "consecutive" or when it was explicitly described that all eligible patients were approached for inclusion in the study C: The follow-up time for blood loss/transfusion should be explicitly stated (e.g., "for 24 h," "until discharge") and in accordance with the objective of the study, e.g., sufficient time for follow-up if postoperative blood loss was investigated G: "Treatment" is here defined as treatment of bleeding, e.g., transfusion, antifibrinolytic agents, etc. patients on antiplatelet or anticoagulant medication and are grouped separately, [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] while the remaining 18 studies investigated only standard coagulation tests. [97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] We considered a rating of 14 or above to be of good quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicated that LTPR, measured by some PFTs is also an independent risk factor for bleeding. 3,18,66,[74][75][76][77][78] LTPR is associated with a higher incidence of thrombolysis in myocardial infarction major bleeding (2.2 vs. 0.8%; p ¼ 0.005). 76 Sibbing and colleagues studied 2,533 patients undergoing PCI using multiplate assay and found that 38% of patients with LTPR to clopidogrel had significantly higher incidence of bleeding (adjusted OR, 3.5; 95% CI, 1.6-7.3; p ¼ 0.001).…”
Section: Assessment Of Effects Of Antiplatelet Therapy In High-risk Pmentioning
confidence: 99%